Fully atomistic modeling of plasmonic bimetallic nanoparticles: nanoalloys and core-shell systems - Nicoli, Luca; Lafiosca, Piero; Grobas Illobre, Pablo; Bonatti, Luca; Giovannini, Tommaso; Cappelli, Chiara (Frontiers in Photonics, 2023)
The recently developed ωFQFµ model (ACS Photonics, 9, 3025-3034) is extended to bimetallic nanoparticles, such as nanoalloys and core-shell systems. The method finds its grounds in basic physical concepts, such as Drude conduction theory, electrostatics, interband transitions, and quantum tunneling. The approach, which is parametrized on ab-initio simulations of Ag-Au nanoalloys, is challenged against complex Ag-Au nanostructures (spheres, nanorods, and core-shell nanoparticles). Remarkable agreement with available experimental data is found, thus demonstrating the reliability of the newly developed approach.